SAT0260 Ovarian function preservation with gonadotropin-releasing hormone analogues in patients with systemic lupus erythematosus treated with cyclophosphamide. (15th June 2017) - Pacucci, VA; Ceccarelli, F; Perrone, G; Zannini, I; Candelieri, M; Leccese, I; Perricone, C; Miranda, F; Truglia, S; Spinelli, FR; Alessandri, C; Valesini, G; et al.
Abstract : Background: The fertility in childbearing Systemic Lupus Erythematosus (SLE) patients can be impaired due to several conditions. In particular, treatment with alkylating agents, as cyclophosphamide (CYC), could determine menstrual irregularities and premature ovarian failure (POF). Gonadotropin-releasing hormone analogues (GnRH-a) is one of the preventive strategy suggested by the recently published EULAR recommendations (1). They are characterized by good safety profile and effectiveness in reducing POF rate in patients with malignancies and autoimmune diseases. So far, only few studies have been published focusing on the use of GnRH-a to prevent POF in SLE women receiving CYC treatment. Objectives: In the present case-control study, we aimed at evaluating the efficacy of GnRH-a on the ovarian function preservation in SLE patients treated with CYC. Methods: We enrolled consecutive SLE patients, fulfilled the 1997 ACR revised criteria treated with CYC in the period between 2005 and 2012, receiving GnRH-a (GnRH-a+). As control, SLE patients treated with CYC not receiving GnRH-a (GnRH-a-) were assessed. Clinical and laboratory data were collected in a standardized, computerized and electronically filled form. Ovarian function was assessed by the evaluation of FSH and estradiol level (E2). GnRH-a (triptorelin 3.75 mg/monthly intramuscularly) was prescribed. SLE patients treated with CYC were followed after the treatment every six months during the first year and then annually. Results: Thirty-tree SLE patients treated by CYC were evaluated in the present analysis: 75.7% of patients were treated for lupus nephritis. Among [FC1] these, 18 GnRH-a+ (mean±SD age 29.3±7.6 years; mean±SD disease duration 7.2±4.2 years) and 15 GnRH-a- (mean±SD age 31.0±10.5 years; mean±SD disease duration 6.3±7.4 years). The mean±SD SLEDAI-2K score in GnRH-a+ patients was 10.1±3.7, in GnRH-a- patients 8.3±3.3 (p=NS). Moreover, no differences were identified concerning the duration of CYC treatment (GnRH-a+: 6.1±2.8 months versus GnRH-a- 6.1±2.2 months, p=NS) and follow-up (GnRH-a+: 8.11±2.2 years versus GnRH-a- 9.3±7.2 years, p=NS). The prevalence of POF was significantly higher in GnRH-a- (5 patients, 33.3%) in comparison with GnRH-a+ (2 patients, 11.1%, P=0.0002). A significantly higher mean age at the time of CYC treatment was observed in patients developing POF (37.7±5.9 years) in comparison with those not developing this complication (28.0±8.5 years, p=0.008). Moreover, the use of GnRH-a seems to be protective also in terms of menstrual cycle regularity: the cycle remained regular during treatment in 83.3% of GnRH-a+ and only in 33.3% of GnRH-a- (p=0.003). During the follow-up, 3 patients in the GnRH-a+ group underwent pregnancy, with a good outcome. Conclusions: The results of the present study showed the protective role of GnRH-a for the preservation of ovarian function in SLE patients treated by CYC. Furthermore, the age resulted the only risk factor associated with POF development. References: Andreoli L. et al. Ann Rheum Dis. 2016 Jul 25. Disclosure of Interest: None declared